2004
DOI: 10.1023/b:joih.0000014638.87569.2e
|View full text |Cite
|
Sign up to set email alerts
|

Latinos' Health Care Access: Financial and Cultural Barriers

Abstract: This study aimed at investigating how income, culture, and language affect health care access. Data from a structured questionnaire administered to a random sample of 206 Latinos was analyzed using multivariate logistic regression. Qualitative data served to explain quantitative results. Point estimates for various access measures were similar to national data. In multivariate logistic regression, income and education determined having health insurance (OR 6.8 and 7.4; 95% CI 2.7-17.3 and 2.9-19.0, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 20 publications
1
70
0
3
Order By: Relevance
“…While all participants had at least one support person with them during delivery, none of the uninsured women had a support person that was there continuously for the labor and delivery, or had extended family support during the postpartum time. This lack of support is further enhanced by the existing social isolation in NGA, where social and support networks are not as well developed, as compared to non-NGA [2,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While all participants had at least one support person with them during delivery, none of the uninsured women had a support person that was there continuously for the labor and delivery, or had extended family support during the postpartum time. This lack of support is further enhanced by the existing social isolation in NGA, where social and support networks are not as well developed, as compared to non-NGA [2,8].…”
Section: Discussionmentioning
confidence: 99%
“…Unfamiliarity with the US health care system, communication barriers, and social isolation negatively impact Latino health in NGA, leading to conditions which could foster poor physical and mental wellbeing [2,[7][8][9][10]. Additionally, insurance status impacts the health of Latinos, as Latinos have the highest uninsured rates of any other racial or ethnic group in the USA [11].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the main reasons for lower affiliation with a PCP for people with high education should be explored in further studies. Research has found that education inversely affects satisfaction with care received [67]. Less satisfaction with the quality of primary care (access and/ or patient-centeredness) may lead to a lower probability of highly educated people being affiliated with a PCP.…”
Section: Principal Findingsmentioning
confidence: 99%
“…For example, research from the US has shown that ethnic minority and immigrant groups may choose to go without a regular source of care because they trust God to protect them from illness, they lack appropriate information or because they regard health services as cold and disinterested [67,68]. Hence, consideration of cultural factors in health policy is warranted.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Es una realidad que, en ocasiones, las diferencias entre sanitarios y pacientes crean a veces barreras y situaciones tensas durante la atención sanitaria 11,12 .…”
Section: Los Profesionales De La Salud Y Atención Sanitaria a Los Inmunclassified